ANALISIS KEBIJAKAN MENGENAI KETENTUAN KUHP DAN KUHAP TENTANG HAK-HAK KORBAN KEJAHATAN - Ferdricka Nggeboe (Jurnal LEX SPECIALIS, 2010)
AbstractThat the crime is greatly enhanced both in terms of quantity and its quality. An increasingly complex conditions not only make a lot of conflicting interests. The struggle will be fine but always wanted to under-unite these demands should be coupled with legal protection as a basic struggle to obtain fair treatment for an act or result of criminal act itself. The discovery that the perpetrators of crime as any other human being who should be protected on behalf of human rights more regulated in the Penal Code and Criminal Procedure Code, but viewed from the other side of so many victims that it does not get his rights, whether by conviction of perpetrators of crime victims' rights are met what about the losses suffered by victims, things are not yet properly addressed in the Criminal Code and Criminal Procedure Code as a sense of justice.SimakBaca secara fonetik